Characterization of Helicobacter Pylori Infection in Patients with Gastric Ulcer - Marcos Félix Osorio Pagola; Magalys Blanca Olivert Cruz; Juan Luís de Pasos Carrazana; Alfredo Basilio Quiñones Ceballos; Mabel Vega Galindo; Anagalys Ortega Alvelay (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Nowadays, infection due to Helicobacter Pylori is recognized as a medical problem worldwide. It causes chronic gastritis, peptic ulcer disease, lymphatic proliferative disorders and it is a risk factor for gastric cancer. Objective: To characterize Helicobacter Pylori infection in patients with gastric ulcer and to relate this infection to gastric histological diagnoses. Methods: An observational, descriptive, correlational retrospective study in patients with gastric ulcers at the Dr.Gustavo Aldereguía Lima Hospital was carried out from January 2005 to December 2007. Endoscopy and mucous gastric biopsy were performed for the histological and diagnostic study of the infection due to Helicobacter Pylori by means of the hematoxiline-eosine and giemsa stain respectively. The sample was composed by 137 patients. Results: the frequency of infection due to Helicobacter pylori was 59,1 % prevailing in the age groups 51-60 years old (34,6 %) and 61-70 yearsold. (30,8 %). The highest frequency of malignant ulcers were located at the antral region (85,7 %) with predominance of Helicobacter Pylori (80 %). There was a 95 % reliability between the relationship of Helicobacter Pylori and the histological diagnoses. The patients under the diagnosis of Helicobacter Pylori showed a greater probability to present cancer (OR 4,32 IC: 0,58-39,44) and worsened chronic gastritis (OR 2,59 IC: 0,61-11,30). Chronic gastritis did not constitute a risk factor for acute gastritis(OR 0,86 IC: 0,09-7,08). Conclusions: The probability of suffering from gastric cancer, chronic gastritis and worsened chronic gastritis was greater in all those patients who presented with Helicobacter pylori infection but in this study Helicobacter pylori did not constitute a risk factor for acute gastritis